Behavior of three hypocholesterolemic peptides from soy protein in an intestinal model based on differentiated Caco-2 cell. (June 2018) - Aiello, Gilda; Ferruzza, Simonetta; Ranaldi, Giulia; Sambuy, Yula; Arnoldi, Anna; Vistoli, Giulio; Lammi, Carmen
Graphical abstract: Highlights: IAVPGEVA, IAVPTGVA, and LPYP, 3 soy peptides, are absorbed by Caco-2 cells. A specific LC-MRM method was developed for their quantification. The peptides are in part hydrolyzed to fragments by brush border peptidases. IAVPGEVA, IAVPTGVA, and LPY are substrates of DPP-IV. Abstract: IAVPGEVA, IAVPTGVA, and LPYP, three peptides deriving from soy protein hydrolysis, inhibit the activity of 3-hydroxy-3-methylglutaryl CoA reductase (HMGCoAR) and modulate cholesterol metabolism in HepG2 cells. In order to assess whether these hypocholesterolemic peptides can be absorbed across the epithelium barrier, experiments were performed using human intestinal Caco-2 cell monolayers grown in two-compartments systems. Each peptide (500 µM) was incubated in the apical compartment for a time spanning from 15 to 120 min and quantified in the basolateral compartment using a highly sensitive LC-MRM method. The peptides were partially absorbed across the Caco-2 monolayers, but they were also hydrolyzed to shorter fragments by brush border peptidases. Possibly dipeptidyl peptidase IV, the main protease expressed on differentiated cells, had not a main role in this metabolism, since these peptides act as competitive inhibitors of this enzyme. In silico docking simulations suggested that some metabolites may retain a hypocholesterolemic activity.